Penentuan Lokasi Tempat Pengelolaan Sampah Terpadu (TPST) di Kabupaten Blitar - Erwin Eka Kurniawan (Fakultas Teknik, 2025)
Blitar Regency has problems in waste management, this can be seen from the amount of waste volume that is recycled is not proportional to the amount of waste volume generated. This condition is caused by inappropriate waste processing infrastructure, because currently it only has 3 landfills with the amount of waste volume that has exceeded capacity. Waste recycling facilities are only carried out in one place, namely the Tegalasri landfill with limited waste processing volume, while the other two places, namely the Kendalrejo and Pagerwojo landfills, do not have waste recycling facilities. If this condition is not addressed immediately, it will have a negative impact on the environment and human health. Efforts that can be made are to build a better waste management site in the form of an Integrated Waste Management Site which is a waste management site that can run sustainably. The selection of integrated waste management site locations is carried out based on the technical provisions of SNI-03-3241-Year 1994 and adjustments to the Minister of Public Works and Spatial Planning Regulation No. 3 of 2007, as well as previous research related to the selection of landfill sites. The analysis method used is spatial analysis through scoring and weighting processes, as well as making observations through maps. In addition, analysis using the Likert scale method was also used to select locations that had been identified based on government and community stakeholders. Based on the results of the research, there are 4 locations that meet the parameters with the highest score of 217, namely land 8 located in Pandanarum Village, Sutojayan Subdistrict, in addition there is a total score of 215 consisting of land 1 located in Sumberingin Village, Sanankulon Subdistrict, land 6 in Plosorejo and Darungan Villages, Kademangan Subdistrict, and land 12 in Kedungbunder and Pandanarum Villages, Sutojayan Subdistrict. Based on the Likert scale analysis, there is one land that has a total stakeholder score of 4.66, and gets community approval with a total score of 4.07, namely land 1 with a land area of 11.76.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: Determination; Location; Intergrated Waste Management Center